The Reality of Sustainability of Emerging Cybersecurity Companies in Light of Individuals’ Attitudes in Saudi Society - Alduriweesh, Mohammad Abdulaziz (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to explore the reality of sustainability of emerging cybersecurity companies in the Kingdom of Saudi Arabia in light of individuals’ attitudes within Saudi society, with a focus on the importance of these companies in data protection and the provision of digital security solutions. To achieve the study’s objectives, a descriptive methodology was adopted using a survey approach. Data was collected through a questionnaire distributed to a sample of 250 individuals, divided into two groups: the first group included 170 employees working in emerging cybersecurity companies at both administrative and technical levels, while the second group consisted of 80 beneficiaries of these companies’ services within Saudi society. Using this sample, the study analyzed the attitudes of both groups and their level of trust in the sustainability of these companies. The results based on the study’s hypotheses indicated a strong relationship between individuals’ attitudes toward cybersecurity and the extent to which emerging companies apply security standards and policies, which directly contributes to the growth and sustainability of this vital sector in the Kingdom. In light of these findings, the study recommends enhancing public awareness of cybersecurity, investing in the development of human capital, updating legislation in line with technological advancements, and fostering an entrepreneurial environment to support the cybersecurity sector in the Kingdom of Saudi Arabia.